Traceability - Nanna Bonde Thylstrup; Matthew Archer; Louis Ravn (Internet Policy Review, 2022)
Traceability is an increasingly prominent research topic in decentralised technosocial systems in fields as diverse as health, sustainability, finance, and supply chain management. At the same time, traceability connotes different meanings and potentialities within each of these fields. This Glossary article homes in on "traceability" as a concept that is deceptively simple but fundamentally crucial in blockchain technologies. First, the entry provides an overview of the historical background of traceability within digital technologies. The entry then outlines the most critical dimensions of the concept by relating the term to questions about accountability, explainability, and speculation. Finally, emergent methodological and theoretical insights concerning traceability as a paradoxical concept in distributed technologies are highlighted.
Keywords: 300; Traceability; Tracing app; Message tracing; Accountability